Lymphocyte mitogenic transformation is accompanied by phosphorylation of the nucleolar transcription factor UBF - Kalousek, I; Krízková, P (Cellular and molecular biology (Noisy-le-Grand, France), 2000)
Lymphoid cell stimulation with phytohemagglutinin, converting quiescent lymphocytes into rapidly-proliferating lymphoblast-like cells, is tightly coordinated with the transcription of ribosomal genes. Nuclear Run-On assays demonstrated that after the addition of PHA ribosomal gene activity increased rapidly during the first 40 hrs. and within 64 hrs. it reached its maximum. In contrast, UBF1 and UBF2 intracellular levels, examined in immunoblots, paralleled DNA replication/cell proliferation activity. During the first 40 hrs. following the addition of PHA, lymphocytes did not proliferate and UBFI and UBF2 levels nearly corresponded to that found in quiescent cells. However, the UBF1 and UBF2 intracellular contents increased nearly twofold in the interval from 40 to 64 hrs. Metabolic radiolabeling with 32P-orthophosphate showed that in quiescent lymphocytes the cellular pool of UBF proteins was in an underphosphorylated state. Within the first 40 hrs. after the addition of PHA the phosphorylation of underphosphorylated UBF1 and UBF2 pools predominated over the phosphorylation of very small amounts of neosynthesized UBF molecules. Subsequently, within the time period from 48 to 64 hrs. the phosphorylation of neosynthesized UBF proteins predominated. We speculate that the phosphorylation-mediated mobilization of the inactive underphosphorylated intracellular UBF pool during the G1 phase of the first cell division cycle is implicated in the ribosomal RNA synthesis acceleration and in the transformation of quiescent lymphocytes to lymphoblast-like proliferating cells.
Keywords: DNA vazebné proteiny; buněčné dělení; RNA ribozomální; lymfocyty; Mitogens; transkripční faktory; Up-Regulation; transkripční iniciační komplex Pol1 - proteiny; prekurzory RNA; Lymphocyte Activation; aktivace lymfocytů; DNA; lidé; mitogeny; fytohemaglutininy; Pol1 Transcription Initiation Complex Proteins; upregulace; Transcription Factors; kultivované buňky; RNA, Ribosomal; Cells, Cultured; fosforylace; DNA-Binding Proteins; RNA Precursors; Lymphocytes; Phytohemagglutinins; Cell Division; Phosphorylation; Humans